2020
DOI: 10.6066/jtip.2020.31.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Pemetaan Karakteristik Kimia Biji Kopi Arabika Gayo Dan Robusta Gayo

Abstract: The distinctive aroma and taste of roasted coffee can b e due to varietal differences in green coffee b eans. The purpose of this research was to map the chemical characteristics of green coffee b eans of Gayo arab ica and Gayo rob usta using principal component analysis (PCA) approach. Other analyses include pH using pH meter, total fats b y Soxhlet method, total ash b y gravimetric method, total protein b y Kjeldahl method, total carb ohydrates b y difference, total solub le solids (TSS) b y refractometer, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…In this study, it was proved that wine coffee that was fermented longer (hard coffee wine) had a lower pH of 4.65 than hard and soft wine coffee, which were 4.76 and 4.87, respectively. The length of fermentation in general causes the pH value of wine coffee lower than the pH of Gayo Arabica coffee beans which are generally above 5 [17].…”
Section: Resultsmentioning
confidence: 95%
“…In this study, it was proved that wine coffee that was fermented longer (hard coffee wine) had a lower pH of 4.65 than hard and soft wine coffee, which were 4.76 and 4.87, respectively. The length of fermentation in general causes the pH value of wine coffee lower than the pH of Gayo Arabica coffee beans which are generally above 5 [17].…”
Section: Resultsmentioning
confidence: 95%
“…According to research [46], coffee beans contain higher protein than roasted coffee based on total amino acids.Several amino acids will react to form coffee's aroma and color components. Therefore, the amino acids in coffee beans determine the qualities of roasted coffee [47]. Measuring protein levels in coffee can be done using the Lowry method.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Robusta coffee bean samples appeared to have a slightly lower pH than the Arabica samples. Saputri et al (2020) reported that Arabica Gayo coffee beans have an average pH of 5.66, which is slightly higher than that of Robusta Gayo coffee beans (4.89). However, Lee et al (2017) reported that the pH of Arabica coffee beans is lower (4.60-5.60) than that of Robusta coffee beans (5.30-6.10).…”
Section: Total Carbohydrate Contentmentioning
confidence: 93%